2022
DOI: 10.1136/bmjopen-2021-049951
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility, psychological outcomes and practical use of a stress-preventive leadership intervention in the workplace hospital: the results of a mixed-method phase-II study

Abstract: ObjectivesHospitals are psychologically demanding workplaces with a need for context-specific stress-preventive leadership interventions. A stress-preventive interprofessional leadership intervention for middle management has been developed. This phase-II study investigates its feasibility and outcomes, including work-related stress, well-being and transformational leadership.DesignThis is a mixed-methods study with three measure points (T0: baseline, T1: after the last training session, T2: 3-month follow-up)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Although most aligned with health-orientated leadership interventions [10][11][12] outcomes were not always geared to health and well-being of the leader or staff. Nor were goals primarily geared to effect change in the organisation (an indirect effect).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most aligned with health-orientated leadership interventions [10][11][12] outcomes were not always geared to health and well-being of the leader or staff. Nor were goals primarily geared to effect change in the organisation (an indirect effect).…”
Section: Resultsmentioning
confidence: 99%
“…Yet, studies of health-orientated leadership interventions in health care are sparse. 11,13 A systematic review yielding only seven studies showing mixed, but weak evidence for effect on mental health of leaders and/or staff. 13 Two studies showed significant positive trends for leaders' mental health.…”
mentioning
confidence: 99%
“…Few interventions targeting the leadership competencies of nurse leaders have been found to assess and report on the impact the interventions have on leaders' stress levels and overall psychological functioning. A recent German study of 93 middle management leaders from a tertiary hospital, which evaluated the impact of a stress-preventive leadership intervention, reported improvements in well-being ( Stuber et al, 2022 ). An intervention study focusing on servant leadership offered to 42 senior nursing managers in one acute general hospital in Hong Kong ( Luk, 2018 ) suggested improvements in work-related well-being and work satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…[117]; 93 leaders of different professions from a tertiary hospital in Germany. [118]; Arabic version of WHO-5 was used with 200 patients from six rural PHC settings in the Ismailia, Egypt governorate. [119]; 1,164 employees nested in 30 workplaces in Canada.…”
Section: Recommendations For Assessing Well-beingmentioning
confidence: 99%